2009
DOI: 10.1111/j.1399-6576.2009.02015.x
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital therapeutic hypothermia for comatose survivors of cardiac arrest: a randomized controlled trial

Abstract: Spontaneous cooling alone is insufficient to induce therapeutic hypothermia before hospital admission. Infusion of ice-cold fluid after return of spontaneous circulation was found to be well tolerated and effective. This method of cooling should be considered as an important first link in the 'cold chain' of prehospital comatose cardiac arrest survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 32 publications
2
82
0
3
Order By: Relevance
“…[10][11][12][13] Metaanalysis demonstrated that therapeutic mild hypothermia improved neurological function and survival to hospital discharge compared with normothermia. Some clinical trials in China also showed that therapeutic mild hypothermia improved neurological function and longterm prognosis in patients successfully resuscitated from CA.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Metaanalysis demonstrated that therapeutic mild hypothermia improved neurological function and survival to hospital discharge compared with normothermia. Some clinical trials in China also showed that therapeutic mild hypothermia improved neurological function and longterm prognosis in patients successfully resuscitated from CA.…”
Section: Discussionmentioning
confidence: 99%
“…[59] Several small randomized trials, and nonrandomized observational and retrospective trials, looked at prehospital cooling initiation for patients with OHCA with large-volume ice-cold (4°C) fluids (discussed in more detail in a separate chapter: Prehospital Therapeutic Hypothermia for Cardiac Arrest). [60][61][62][63][64][65][66][67][68] All these studies documented the safety and feasibility if ice-cold fluids for the rapid induction of therapeutic hypothermia. Other promising methods for induction of hypothermia include transnasal cooling device [69] , self-adhesive cooling pads [70] , and cranial cooling caps.…”
Section: Methods For Induction Of Therapeutic Hypothermiamentioning
confidence: 99%
“…Letztendlich könnte der Nutzen am größten sein, wenn bereits während des Kreislaufstillstands mit der Kühlung begonnen wird; Labordaten deuten darauf hin, dass dies den ROSC sogar erleichtert [754,755]. Verschiedene klinische Studien konnten zeigen, dass die Hypothermie präkli-nisch eingeleitet werden kann [511, 729,730,732,741], allerdings gibt es bis bisher keine klinischen Daten, die belegen, dass ein rasches Erreichen der Zieltemperatur zu einem besseren Outcome führt. In einer registerbasierten Fallserie mit 986 komatösen Patienten nach Kreislaufstill-stand war der Zeitpunkt des Kühlungs-beginns nicht mit einem besseren neurologischen Outcome nach Krankenhausentlassung assoziiert [666].…”
Section: Temperaturkontrolleunclassified